About the science-theoretical measuring of history of revolutionary shocks in Russia (to the 100 year of February and October, 1917) - Andrey V. Ishin (Проблемы постсоветского пространства, 2017)
The article is devoted the comprehension of the science-theoretical tool of research of revolutionary shocks in Russia. The 100-years-old anniversary of revolutionary shocks in Russia pulls out before researchers the vital task of complex comprehension of reasons, character and consequences of revolution. Scientific tasks which stood before the scientists of soviet epoch lay mainly inplane illumination of event of revolution and Civil war as displays of fight of «leading revolutionary class» — proletariat at the head with bolshevist communist party with «regressive classes» — bourgeoisie, squires, clergy, the «kulak». Within the framework of this main approach, researchers succeeded to form the fully integral scientific picture of social and political conflict of 1917-1922 years, on the whole to expose his motive forces, leading political actors, to trace the dynamics of events.However and presently to a full degree the task of comprehensive scientific analysis of structural-functional features of becoming and evolution of organs of power saves the actuality, which functioned within the framework of the different political modes, including modes of antibolshevist orientation. The important element of search is an exposure of specific of mutual relations of public institutions, basic directions of policy, historical factors which stipulated acceptance and practical realization of important administrative decisions.Іnstitucional approach must organically complement dominant to this day in scientific literature historical-event approach. Institucional approach consists in that a look to the social and political process is inplane not «from» (as in the historical-event measuring) outside, and, vice versa, «from within». In obedience to this approach, research attention applies foremost on subsoil and on organization of administrative mechanisms, internal logic of acceptance both key and, on the face of it, second-rate decisions, tracing of consequences of these decisions, in the nearest and remote historical prospect. The system of organization of power, accentuation of certain valued orientiriv, character of co-operation, between leading organs acquire the value of major (and sometimes decision) factor of social and political process. Important advantage offered approach is that he allows expressly to realize the «central nerve» of epoch, trace the change of socialideological dominants, transformation of management methods.Within the framework of institucional approach an author grounds the use of term «fragmentation of power». An author shows that this term is more unitversal, than term «diarchy», which presently prevails in scientific literature. In the article the fundamental differences of term come to light «fragmentation of power» from a term «diarchy».